Two new species of Sida (Malvaceae: Malvoideae) for Brazil - Bovini, Massimo G. (Phytotaxa, 2016)
Two new species of Sida (Malvaceae) found in the state of Minas Gerais, southeastern Brazil are described and illustrated: S. oblonga and S. carrascoana, which belong to the sections Cordifoliae and Muticae, respectively. Both are compared to related species, and have their conservation status evaluated.